Transcriptomic analysis reveals the functions of H2S as a gasotransmitter independently of Cys in Arabidopsis - Fang, Huihui; Yu, Zhenyuan; Xing, Kehong; Zhou, Lingyi; Shao, Yuke; Zhang, Xiaofang; Pei, Yanxi; Zhang, Lu (Frontiers in Plant Science, 2023)
Numerous studies have revealed the gasotransmitter functions of hydrogen sulfide (H2S) in various biological processes. However, the involvement of H2S in sulfur metabolism and/or Cys synthesis makes its role as a signaling molecule ambiguous. The generation of endogenous H2S in plants is closely related to the metabolism of Cys, which play roles in a variety of signaling pathway occurring in various cellular processes. Here, we found that exogenous H2S fumigation and Cys treatment modulated the production rate and content of endogenous H2S and Cys to various degrees. Furthermore, we provided comprehensive transcriptomic analysis to support the gasotransmitter role of H2S besides as a substrate for Cys synthesis. Comparison of the differentially expressed genes (DEGs) between H2S and Cys treated seedlings indicated that H2S fumigation and Cys treatment caused different influences on gene profiles during seedlings development. A total of 261 genes were identified to respond to H2S fumigation, among which 72 genes were co-regulated by Cys treatment. GO and KEGG enrichment analysis of the 189 genes, H2S but not Cys regulated DEGs, indicated that these genes mainly involved in plant hormone signal transduction, plant-pathogen interaction, phenylpropanoid biosynthesis, and MAPK signaling pathway. Most of these genes encoded proteins having DNA binding and transcription factor activities that play roles in a variety of plant developmental and environmental responses. Many stress-responsive genes and some Ca2+ signal associated genes were also included. Consequently, H2S regulated gene expression through its role as a gasotransmitter, rather than just as a substrate for Cys biogenesis, and these 189 genes were far more likely to function in H2S signal transduction independently of Cys. Our data will provide insights for revealing and enriching H2S signaling networks.